Sorghum - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Crop specialist Casper Moyo advocates intercropping and use of ox-drawn weeders in sorghum production, and stresses the importance of crop spacing and early weeding.